Information Systems Security 8th International Conference, ICISS 2012, Guwahati, India, December 15-19, 2012, Proceedings - Venkatakrishnan, Venkat; Goswami, Diganta (Security and Cryptology ;, 2012)
This book constitutes the refereed proceedings of the 8th International Conference on Information Systems Security, ICISS 2012, held in Guwahati, India, in December 2012. The 18 revised full papers and 3 short papers presented were carefully reviewed and selected from 72 submissions. The papers are organized in topical sections on software security, acces control, covert communications, network security, and database and distributed systems security.